Comparisons of Exercise Dose and Symptom Severity Between Exercisers and Nonexercisers in Women During and After Cancer Treatment - Cho, Maria H. (2012)
CONTEXT: Although numerous studies of the efficacy of exercise are reported, few studies have evaluated changes in characteristics of exercise dose in women with cancer both during and after cancer treatment. OBJECTIVES: To describe the characteristics of exercise dose (i.e., frequency, duration, and intensity), and to evaluate for differences in symptom severity (i.e., fatigue, sleep disturbance, depression, pain) between women who did and did not exercise during and after cancer treatment. METHODS: In a sample of 119 women, two groups were classified: exercisers and nonexercisers. Exercisers were defined as women who met specific criteria for frequency (three times per week), duration (20 minutes per session), intensity (moderate), and mode (aerobic). Nonexercisers were defined as women who did not meet all of these criteria. Evaluation of exercise dose was completed at baseline (T1: the week before chemotherapy cycle two), at the end of cancer treatment (T2), and at the end of the study (T3: approximately one year after the T1 assessment) using self-report exercise questionnaires. RESULTS: Approximately 50% of the participants exercised during and 70% exercised after treatment. At T1, exercisers had lower total fatigue, lower behavioral and sensory subscale fatigue scores, and lower depression scores (P =0.038) than nonexercisers. No significant differences in sleep disturbance or pain were found between groups. At T2, exercisers had lower cognitive/mood subscale fatigue and depression scores than nonexercisers (P =0.047). At T3, no significant differences were found between groups in any symptom severity scores. CONCLUSION: Both during and after cancer treatment, achieving or maintaining exercise guideline levels were met by most patients. Further study is needed to examine the link between exercise dose and symptom severity.